Pancreatic Cancer: Pathogenesis, Diagnosis, and Laboratory Tests - Rikarni Rikarni (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Pancreatic cancer is the eleventh cause of cancer death in Indonesia in 2020. However, pancreatic cancer is the second leading cause of cancer death in the United States after lung cancer. Although it is substantially less common than the other malignancies, pancreatic carcinoma is near the top of the list of killers because it is a highly aggressive cancer. Pancreatic cancer has multistep carcinogenesis, starting from the Pancreatic Intraductal Neoplasia (PanINs IA, IB, II, and III) and is ended with an invasive neoplastic lesion. The different incidence of pancreatic cancer between countries also shows the important role of environmental factors for the disease. A better understanding of the risk factors, genetics, molecular pathogenesis, symptoms associated with this disease, and the laboratory aspect is essential to inform both health professionals and the general population as the potential preventive and/or early detection measures.